A Sketch on Oral Mucosal Lesion Presenting in a Rural Tertiary Care Hospital in Bangladesh (Update Dental College Journal, 2021)
Background: Oral mucosal lesion (OML) is defined as any abnormal alteration in color, surface aspect, swelling, or loss of integrity of the oral mucosal surface. Some oral mucosal lesions are benign and require no treatment but some may present with significant pathology. Several oral potential disorders frequently progress into malignancyObjective: The present study was carried out to assess the pattern of various oral cavity lesions of patients attending in a regional tertiary care hospital in northern area of Bangladesh.Materials and Methods: This prospective cross-sectional study was carried out in the Department of Dentistry in collaboration with department of Pathology of Khwaja Yunus Ali Medical College and Hospital, Sirajgonj, Bangladesh during the period of one year from December 2016 to December 2017. An elaborate schedule was prepared before undertaking the study. A total of 73 patients in the Dental OPD of the hospital presenting with oral lesion for more than 3 weeks were randomly selected. An incisional biopsy was taken from all patients and histological examinations were done. The collected data were analyzed using SPSS (V-20) and MS Excel.Results: Most common site of oral lesion is Buccal Mucosa (36.99%), then supraglotic region (26.03%), lower lip 6.85%, gingiva 5.48%, anterior palate and oral flor 4.11% each. Most of the lesion was Squamous cell carcinoma (58%), then lichen planus, leukoplakia, inflammatory lesion, pyogenic granuloma and verrucous carcinoma, each of them was around 5% of lesion.Conclusion: The epidemiological data on the prevalence of oral lesion is an important determinant in planning appropriate levels of services and further studies are required to provide accurate estimates of the treatment need in Bangladeshi population with oral lesion.Update Dent. Coll. j: 2021; 11(2): 4-9